2023
DOI: 10.3390/bs13020191
|View full text |Cite
|
Sign up to set email alerts
|

Students from a Public School in the South of Chile with Better Physical Fitness Markers Have Higher Performance in Executive Functions Tests—Cross-Sectional Study

Abstract: In the past few years, the level of physical fitness in children has decreased globally. According to the SIMCE test carried out in 2015, 45% of 8th year students in Chile were overweight. Moreover, international studies have shown that being overweight is associated with the development of chronic illnesses, negatively affecting cognitive mechanisms and processes. Nevertheless, there is little to no evidence that analyzes the relationship between physical fitness and executive functions in students, at a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The obtained results reveal statistically significant associations between the analyzed variables, fulfilling the research objective. These findings are in line with previous research that has highlighted the relationships between physical fitness and cognitive functions [23,24,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained results reveal statistically significant associations between the analyzed variables, fulfilling the research objective. These findings are in line with previous research that has highlighted the relationships between physical fitness and cognitive functions [23,24,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, various studies have highlighted the existing relationship between physical fitness and cognitive functions at these ages [20][21][22]. For instance, a study conducted with Chilean students aged 9 to 12 [23] found better results in the gray and color trails test of the Neuropsychological Assessment of Executive Functions Battery for Children (ENFEN) in those students with higher scores in the 20 m shuttle run test, the standing broad jump (SBJ) test, and the 4 m × 10 m shuttle run test from the ALPHA-fitness battery. Another study with students aged 8 to 11 [24] also found associations between cognition and physical activity, assessed through Raven's test and physical speed tests.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of intrinsic mechanism analysis, there is a correlation between muscle strength and executive function, and the effect on the brain may be to alter the excitability of spinal motor neurons and to induce synaptogenesis in the spinal cord (Adkins et al, 2006). In a study of 10‐ to 12‐year‐old children, greater lower extremity body muscle strength and greater upper extremity muscle strength were associated with better working memory, cognitive flexibility, inhibition, planning, and/or attention (Alonso‐Cabrera et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Executive functions are critical to child and adolescent development, enabling children and children and adolescents to effectively focus their attention, multitask, understand and manage their emotions, and enhance their social skills (1)(2)(3). Executive functions are highly correlated with child and adolescent development and are important predictors of behavioral functioning, academic achievement, and even other outcomes such as athletic achievement, academic performance, mental health, social well-being, health, wealth, and quality of life (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%